Respuesta :

9514 1404 393

Answer:

  (2, 3)

Step-by-step explanation:

The coefficients of x are opposites, so the x-terms can be eliminated by adding the two equations together:

  (2x+3y) +(-2x+5y) = (13) +(11)

  8y = 24 . . . simpify

  y = 3 . . . . . divide by 8

Only one answer choice has y = 3: (x, y) = (2, 3).

__

If you like, you can finish the solution by substituting into one of the equations.

  2x +3(3) = 13

  2x = 4 . . . . . . . subtract 9

  x = 2 . . . . . . . . divide by 2

The solution is (x, y) = (2, 3).

_____

A graph confirms this solution.

Ver imagen sqdancefan